Faktor-Faktor yang Memengaruhi Kepuasan Pengguna Website Kampus - Sriwardiningsih, Enggal (Binus Business Review, 2013)
The benefit of internet website is not maximall unless students are satisfied with the campus website. This study proposed and tested model explaining student satisfaction when the website is used as supplementary learning tool of face to face class method. The model is integrated determinants from Media Richness Theory, Self-Determination Theory, Knowledge Based Theory and Attribution Theory, and participant charateristics cited in the research literature. Following a demonstration and using website system in Binus University website system, data were collected from 210 college students. Structural Equation Modelling provided better support for a model that hypothesized stringer effect of website charateristics on e-service quality, motivation, and culture on using internet consumer satisfaction.